The Synthesis and Origin of the Pectic Polysaccharide Rhamnogalacturonan II – Insights from Nucleotide Sugar Formation and Diversity - Bar-Peled, Maor; Urbanowicz, Breeanna R.; O'Neill, Malcolm A. (Frontiers in Plant Science, 2012)
There is compelling evidence showing that the structurally complex pectic polysaccharide rhamnogalacturonan II (RG-II) exists in the primary cell wall as a borate cross-linked dimer and that this dimer is required for the assembly of a functional wall and for normal plant growth and development. The results of several studies have also established that RG-II structure and cross-linking is conserved in vascular plants and that RG-II likely appeared early in the evolution of land plants. Two features that distinguish RG-II from other plant polysaccharides are that RG-II contains 13 different glycoses linked to each other by 22 different glycosidic linkages and that RG-II is the only polysaccharide known to contain apiose and aceric acid. Thus, one key event in land plant evolution was the emergence of genes encoding nucleotide sugar-biosynthetic enzymes that generate the activated forms of apiose and aceric acid required for RG-II synthesis. Many of the genes involved in the generation of the nucleotide sugars used for RG-II synthesis have been functionally characterized. By contrast, only one putative glycosyltransferase involved in the assembly of RG-II has been identified. Here we provide an overview of the formation of the activated sugars required for RG-II synthesis and point to the possible cellular and metabolic processes that could be involved in assembling and controlling the formation of a borate cross-linked RG-II molecule. We discuss how nucleotide sugar synthesis is compartmentalized and how this may control the flux of precursors to facilitate and regulate the formation of RG-II.